THE INFLUENCE OF SERVICE QUALITY AND RELATIONSHIP QUALITY ON CUSTOMER LOYALTY IN TELECOMMUNICATION PROVIDER TRI - Patanduk, Samuel Ray (Universitas Sam Ratulangi, 2016)
Telecommunication industry in Indonesian has shown rapid growth in its availability and content. Based on that condition, the potential market of communications in Indonesia is almost unlimited. The aims of this study are to analyze the influence of service quality and relationship quality on customer loyalty in telecommunication provider Tri. This research is important for company to understand the characteristics of their consumers and customer loyalty on their products. Having understood them, the company’s financial performances then will be affected. This research is causal type of research which uses primary data obtained through questionnaires and uses Multiple Regression Analysis. The population observed is people in Manado who have use Tri provider with 100 respondents as the sample size. The result of this study shows that service quality and relationship quality have significant influences on customer loyalty. To increase customer loyalty, the recommendations for Tri provider are to build stronger and wider network and offer more something valuable to consumer in service interaction process, such as reward and promotional offers, in order to gain customer loyalty. Management of Tri provider needs to hear dissatisfaction, complaints, and advices from their customers. And management of Tri provider can used social media such as twitter, facebook, or own website to know what the customer talk about. Keywords: customer loyalty, service quality, relationship quality